Pre-Cal

posted by .

1) Solve the equation exactly for x:

log3 x - log3(x-3) = 2

I got 1 as an answer. Is this correct?

2) Find the cotangent of the base angle of an isosceles right triangle.

sqrt3 / 2. Is this correct?

  • Pre-Cal -

    1) it is not correct. The second term would be log3(-2) and you can't take the log of a negative number.

    2) it is not correct. The base angle would be 45 degrees, so the cotangent would be 1.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Calculus

    Find the inverse of each relation: y = (0.5)^(x+2) and y = 3log base 2 (x-3) + 2 For the first one I got y=log base 0.5 (x+2)...but the answer in the back of the textbook says that it is not x+2, but x-2. Can someone tell me why it …
  2. Math

    (I have two questions) 1. Solve for x without a calculator: log3(x^2)=2log3(4)-4log3(5) This is what I have so far: 2log3(x)=log3(4^2)-log3(5^4) 2log3(x)=log3(16/625) ...and now I'm stuck. 2. Simplify: 2log4(9)-2log3 <--how do you …
  3. Precalculus

    Please help me with these questions ASAP!! Suppose that f(x)=log3(x-1) a)If f(6)=1.4 and f(8)=1.7,then evaluate log3(35) and log3(7/5). b)If f(3)=0.6, find log9(2).
  4. math (pre-calc)

    Solve for x: 1. 3^2x+3^x+1-4=0 2. log3(x=12)+log3(x+4)=2 3. lnx+ln(x+2)=4 4. 3*4^x+4*2^x+8=0
  5. calculus

    1) Solve for x in terms of k: log3(x) + log3(x+7) = k; 3 is the base 2) e^(x+5) = e^(x) + 6, solve for x. Please help, I have no idea how to do these and I've tried several times!
  6. Math

    Solve for x. log3(x+7)=2-log3(x-1) Write the exact answer using base-10 logarithms.
  7. Algebra

    Solve the equation. 2log3 y = log3 4+ log3 (y+8) Here's what ive got take out the logs and say y^2= 4+ y +8 which simplifies to (y^2)-y=12 how do i simplfy the y?
  8. Math

    Solve the logarithmic equation. Express your solutions in exact form only. Please show all of your work. log3(x+2) + log3(x+8) – 2 = log3(x+3)
  9. Pre-calculus

    Hi i need to find x in 9^(2x-6)=6^(8x-5) So what i did was: 3^(4x-12)=6^(8x-5) log3(3)^(4x-12)=log3(6)^(8x-5) 4x-12=(8x-5)log3(6) now i'm stuck. and i actually feel that the whole thing is wrong. help, pls
  10. Pre-Calc

    Solve the following algebraically. log3(x) + log3(x-2) = 1 Are the solutions 3 and -1?

More Similar Questions